2015
DOI: 10.1002/bjs.9861
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between preoperative anaemia and mortality after surgery

Abstract: Preoperative anaemia is associated with poor outcomes after surgery, although heterogeneity between studies was significant. It remains unclear whether anaemia is an independent risk factor for poor outcome or simply a marker of underlying chronic disease. However, red cell transfusion is much more frequent amongst anaemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
294
2
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(345 citation statements)
references
References 46 publications
13
294
2
21
Order By: Relevance
“…A meta-analysis including almost 950,000 noncardiac surgical procedures reported that preoperative anemia was linked to an increased risk of perioperative transfusion, morbidity (acute myocardial infarction, ischemic stroke, or kidney injury), and hospital and 30-day mortality [9]. In cardiac surgical procedures, preoperative anemia has also been shown to synergize with the negative effects of major blood loss and RBCT on mortality risk [10].…”
Section: Prevalence and Consequences Of Perioperative Anemiamentioning
confidence: 99%
“…A meta-analysis including almost 950,000 noncardiac surgical procedures reported that preoperative anemia was linked to an increased risk of perioperative transfusion, morbidity (acute myocardial infarction, ischemic stroke, or kidney injury), and hospital and 30-day mortality [9]. In cardiac surgical procedures, preoperative anemia has also been shown to synergize with the negative effects of major blood loss and RBCT on mortality risk [10].…”
Section: Prevalence and Consequences Of Perioperative Anemiamentioning
confidence: 99%
“…This correlation between anaemia and renal function is explained by the fact that both anaemia and renal disease are risk factors for ARF. 30 Moreover, LHTC patients were more likely to have lower systolic and mean arterial pressures, which are also risk factors for ARF.…”
Section: Discussionmentioning
confidence: 99%
“…12 The aetiological reason for this is unclear, perhaps representing a surrogate marker for generalised ill health. Whether correction of preoperative anaemia improves postoperative mortality merits further investigation.…”
Section: Discussionmentioning
confidence: 99%